2002
DOI: 10.1046/j.1439-0531.2002.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Ability of Three Radioimmunoassay to Detect Pregnancy‐associated Glycoproteins in Bovine Plasma

Abstract: Pregnancy-associated glycoproteins (PAGs) constitute a large family of glycoproteins that are synthesized in the superficial layer of the ruminant placenta according to a spatial and temporal expression pattern. When PAGs are released in the maternal blood they can be used for pregnancy diagnosis, pregnancy follow-up and for the monitoring of the trophoblastic function. Three different radioimmunoassay systems (RIA 1, RIA 2 and RIA 3) using antisera produced against PAG I67 (RIA 1), PAG55+62 (RIA 2) and PAG55+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 21 publications
6
58
2
Order By: Relevance
“…I) to probe all fractions issued from the DEAE column, and notably used antibodies raised against caprine PAG [18]. In 2002, Perenyi et al [24] stated that RIA-2 and RIA-3 were better for detecting PAG molecules released between days 30 and 70 in pregnant cows and suggested that the antisera used in these assays (raised against caPAG55+59 and caPAG55+62) are better for detecting PAGfamily members. Using the same antisera in double radial immunodiffusion assays, we recently found them to detect more effectively than the antiserum used in RIA-1 ovine PAG present at relatively low concentration in crude sheep placental extracts [25].…”
Section: Discussionmentioning
confidence: 99%
“…I) to probe all fractions issued from the DEAE column, and notably used antibodies raised against caprine PAG [18]. In 2002, Perenyi et al [24] stated that RIA-2 and RIA-3 were better for detecting PAG molecules released between days 30 and 70 in pregnant cows and suggested that the antisera used in these assays (raised against caPAG55+59 and caPAG55+62) are better for detecting PAGfamily members. Using the same antisera in double radial immunodiffusion assays, we recently found them to detect more effectively than the antiserum used in RIA-1 ovine PAG present at relatively low concentration in crude sheep placental extracts [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus the assay gave relative PAG concentrations which were used to differentiate between pregnant and non-pregnant ewes [21]. The procedures and the validation criteria of the assay were similar to those of Perényi et al [24] and are described elsewhere [21]. The cut-off value of the PAG-RIA test used to detect pregnant ewes was ≥ 1 ng·mL -1 [21].…”
Section: Pag Radioimmunoassaymentioning
confidence: 99%
“…During gestation of cow, the concentrations of PAG are detectable as early as from the 19 th to 22 nd days after the conception, to reach concentrations from 3 to 6 ng/ml in the neighborhoods of the 33 rd to 37 th days of gestation [55,56] reported that PAG concentrations increased continuously from day 20 of pregnancy until day 240 followed by a dramatic increase in the last ten days of pregnancy with maximum concentrations between day 5 and day 1 prepartum. In the bovine species, two different patterns of expression were found -those PAG that are expressed predominantly in binucleated cells (PAG 1-subgroup) are invariably absent in term placenta, whereas those PAG expressed more uniformly throughout trophoectoderm (PAG 2-subgroup) are detectable at all stages of pregnancy [57].…”
Section: Pregnancy Associated Glycoprotein (Pag)mentioning
confidence: 99%